2006
DOI: 10.1359/jbmr.051008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Loci From CAST/EiJ Chromosome 1 Affect vBMD Either Positively or Negatively in a C57BL/6J Background

Abstract: Skeletal phenotype analyses of 10 B6.CAST-1 congenic sublines of mice have revealed evidence for the presence of three closely linked QTLs in Chr 1 that influence femoral vBMD both positively and negatively.Introduction: BMD is an important component of bone strength and a recognized predictor of risk for osteoporotic fracture. Our goal in this study was to fine map the chromosomal location of volumetric BMD (vBMD) quantitative trait loci (QTLs) in mouse distal chromosome 1 (Chr 1). Materials and Methods: Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Together, the association and linkage studies point to the fact that osteoporosis susceptibility is determined by a large number of genes with a modest or small effect size and not by few genes of major effect as originally thought. Accordingly, our data with a large number of congenic strains carrying overlapping CAST chromosomal segments from Chr 1 BMD QTL have revealed that there are at least four BMD loci in Chr 1, each contributing to 4%-12% of the variation in peak bone mass (this work and Edderkaoui et al 2006).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Together, the association and linkage studies point to the fact that osteoporosis susceptibility is determined by a large number of genes with a modest or small effect size and not by few genes of major effect as originally thought. Accordingly, our data with a large number of congenic strains carrying overlapping CAST chromosomal segments from Chr 1 BMD QTL have revealed that there are at least four BMD loci in Chr 1, each contributing to 4%-12% of the variation in peak bone mass (this work and Edderkaoui et al 2006).…”
Section: Discussionmentioning
confidence: 62%
“…The rationale for selecting these two inbred mouse strains was based on the fact that these strains are highly polymorphic for genetic differences at >95% of their genomes (Dietrich et al 1996). The B6.CAST F 2 mice were produced and maintained at the animal research facility of The Jackson Laboratory (TJL; Bar Harbor, ME), as previously described (Beamer et al 1999), while the congenic sublines of mice were generated and maintained at the Jerry L. Pettis VA Medical Center (LL; Loma Linda, CA) under the standard conditions previously described by Edderkaoui et al (2006). The animal work performed in this study was approved by the institutional animal care and use committees at both TJL and LL.…”
Section: Methods Micementioning
confidence: 99%
See 3 more Smart Citations